The semantic and aesthetic features of sound and its reflection in children's theater (Al-Academy, 2026)
Children's theater is one of the most important educational theatrical activities that contribute to developing the learner's behaviors, as it constitutes an important tool in crystallizing his ideologies and building his personality, as it plays with his imagination and stimulates his auditory and visual sensory senses and achieves knowledge, entertainment and education, as the research problem centered on the following question: (What are the semantic and aesthetic features of sound and their reflection in children’s theatre?), while the theoretical framework included two chapters, the first: (semantics, aesthetics, sound) between concept and operation, and the second: the concept of children’s theatre, while the third chapter included a review of the research methodology, and the fourth chapter presents the research findings, the most prominent of which are:1. The vocal performance was largely consistent with the scenography of the show, enhancing the semantic and aesthetic quality of the voice, giving it illustrative power, and contributing to the crystallization of the show's events, giving it a dynamic performance and a meaningful aesthetic discourse that impacts children's senses.A number of conclusions emerged, the most prominent of which were:1. The semantic and aesthetic qualities of the voice are achieved through developing a sense of speech in order to create an emotional bridge between the speaker and the child, enabling them to understand the meaning of the speech and feel the emotions. The study concluded with sources.